The roles of Sharia Committee in a Financial Institution in Malaysia / Muhammad Zulhaiqal Hishamuddin - Hishamuddin, Muhammad Zulhaiqal (Academy of Contemporary Islamic Studies (ACIS), 2017)
Generally, Sharia committee is the authorized people who can give instruction, assist and supervise the activities of the financial institution. Although Sharia committee had been established long time before, but many people still not recognized and understood well the roles of Sharia committee precisely. The supervision of Sharia committee in a financial institution plays vital importance roles in order to presume that the products of Islamic banking that the financial institution offered adhere to Sharia supposedly. In addition, the Sharia committee roles in giving guidance for the financial institution in order to implement the products that have been endorsed and approved by Sharia Advisory Council which is the highest authority in Islamic finance. Furthermore, the independence of Sharia committee in develop the Islamic financial structure for the financial institution give the opportunity for the financial institution to expand the products of Islamic banking throughout community and indirectly contribute for mutually consent transaction that had been approved by Allah. This paper also aims to describe broadly, the roles and scopes of works of the Sharia committee in sustaining the operation of the financial institution in Malaysia.